Beethoven's wig - Perlmutter, Richard; Rosetti, Maria (Cambridge, MA : Rounder Books, 2005)
Presents a simplified version of the melody of Beethoven's Fifth Symphony that accompanies a zany adventure story in rhyme, with notes that can be played. Includes CD.
Includes audio CD of vocal and instrumental versions.
Keywords: Beethoven, Ludwig van, -- 1770-1827. -- Juvenile fiction; Beethoven, Ludwig van, -- 1770-1827. -- Fiction; Music appreciation -- Juvenile literature; Children's songs, English -- United States -- Juvenile sound recordings; Music appreciation; Humorous stories